THE USE OF ICE BREAKER TO IMPROVE STUDENTS’ MOTIVATION IN LEARNING ENGLISH AT THE TENTH GRADE STUDENTS OF SMK YPKKP - Rahmayanti, Previa; Saraswati, Putri Ayuna; Bhuana, Gartika Pandu (IKIP Siliwangi, 2019)
There is a belief that ice breaking can be used in the classroom as it provides several advantages for the students. One of them is that it can improve students’ learning motivation. This study aims to prove this belief. In other words, it attempts to investigate the effectiveness of ice breaking in improving students’ learning motivation. Quantitative with one group pretest and posttest was used in this study. The population was the 10th grade students at SMK YPKKP. The sample was one class of office administration major. The data was collected through motivation test adapted from (Burhan, 2017). The result showed that null hypothesis of this study was rejected. It is proved by the data from t-test that shows the sigma 2 tailed is 0.00. This value is less than 0.05. Null hypothesis, therefore, was rejected. This means that ice breaking could definitely improve the students’ motivation in learning English. The teacher therefore can implement it in the classroom. in the title.